A systematic review and meta‐analysis of psychosocial interventions for immigrant and limited English proficient cancer patients. Issue 4 (26th February 2023) - Lui, Florence; Lewicka, Malwina; Bao, George C.; Moyer, Anne; Boyce, Lindsay; Leng, Jennifer
Abstract: Objective: Immigrants, particularly those who are less acculturated and limited English proficient (LEP), often lack access to culturally and linguistically appropriate psychosocial care in cancer survivorship. We sought to determine what psychosocial interventions are available for immigrant and/or LEP cancer patients and to assess treatment and patient factors that may correlate with better psychosocial outcomes for this population. Methods: We conducted a systematic review and meta‐analysis of studies published through August 2022 of interventions conducted with immigrant and/or LEP cancer patients aimed at improving psychosocial outcomes (i.e., quality of life, depression, cancer‐related distress, and anxiety). Using Covidence, a software program for systematic review management, four independent raters screened 16, 123 records with a systematic process for reconciling disagreement, yielding 48 articles (45 studies) for systematic review and 21 studies for meta‐analysis. Results: Most studies were conducted with Spanish‐speaking patients with breast cancer. Study participants ( N  = 5400) were primarily middle‐aged (mean = 53 years old), female (90.0%), and Hispanic (67.0%). The weighted average effect size ( g ) across studies was 0.14 (95% CI 0.03–0.26) for quality of life (18 studies), 0.04 (95% CI −0.08 to 0.17) for depression (8 studies), 0.14 (95% CI −0.03 to 0.31) for cancer‐related distress (6 studies), and 0.03 (95% CI −0.11 to 0.16) for anxiety (5 studies). Conclusion: The interventions under review had small but beneficial effects on psychosocial outcomes for immigrant and LEP cancer patients. Notably, effect sizes were smaller than those found in previous meta‐analyses of psychosocial interventions conducted in majority U.S.‐born, non‐Hispanic White, English‐speaking cancer patient samples. More research is needed to identify key components and adaptations of interventions that benefit immigrant and LEP cancer patients to strengthen their effects for this growing yet underserved population.